The Memory Alteration Test Discriminates between Cognitively Healthy Status, Mild Cognitive Impairment and Alzheimer’s Disease - Custodio, Nilton (2014)
Background/Aims: Dementia is a worldwide public health problem and there are several diagnostic tools for its assessment. The aim of this study was to evaluate the performance of the Memory Alteration Test (M @ T) to discriminate between patients with early Alzheimer’s disease (AD), patients with amnestic mild cognitive impairment (a-MCI), and subjects with a cognitively healthy status (CHS). Methods: The discriminative validity was assessed in a sample of 90 patients with AD, 45 patients with a-MCI, and 180 subjects with CHS. Clinical, functional, and cognitive studies were independently performed in a blinded fashion and the gold standard diagnosis was established by consensus on the basis of these results. The test performance was assessed by means of a receiver operating characteristic curve analysis as area under the curve (AUC). Results: M @ T mean scores were 17.7 (SD = 5.7) in AD, 30.8 (SD = 2.3) in a-MCI, and 44.5 (SD = 3.1) in CHS. A cutoff score of 37 points had a sensitivity of 98.3% and a specificity of 97.8% to differentiate a-MCI from CHS (AUC = 0.999). A cutoff score of 27 points had a sensitivity of 100% and a specificity of 98.9% to differentiate mild AD from a-MCI and from CHS (AUC = 1.000). Conclusions: The M @ T had a high performance in the discrimination between early AD, a-MCI and CHS.